Outbreaks of Acute Necrotic Enteritis and Haemolytic Crisis and Renal Disease Associated with Clostridium perfringens in Captive Toucans (Ramphastos spp). (June 2022) - Juan-Sallés, Carles; Máinez, Mireia; Cortabarría, Nekane; Such, Roger; Adúriz, Gorka; Tello, Montse; Marco, Alberto
Summary: Four toco toucans ( Ramphastos toco ), one channel-billed toucan ( Ramphastos vitellinus ) and one white-throated toucan ( Ramphastos tucanus ) died in two disease outbreaks in the same aviary in 2011 and 2016. Post-mortem examination revealed diffuse necrotic enteritis (NE) as the cause of death of five of these six birds. Clostridium perfringens was identified by culture and real-time multiplex PCR for C. perfringens α-, β-, ε- and ι-toxin genes in ligated intestine of one toucan from each outbreak. At another aviary, two keel-billed toucans ( Ramphastos sulfuratus ) died peracutely from severe haemolytic crisis with haemoglobinaemic nephrosis and cholestasis and acute tubulointerstitial nephritis. Mild NE was present in these birds and C. perfringens was demonstrated in liver by bacterial culture and real-time multiplex PCR for C. perfringens α-, β-, ε- and ι-toxin genes. To the authors' knowledge, this is the first description of outbreaks of NE associated with C. perfringens in captive toucans. Although haemolytic crisis has been reported in humans with C. perfringens type A septicaemia and hepatic abscesses, this presentation appears not to have been described in C. perfringens infections in toucans or other avian species. The factors causing C. perfringens proliferation and disease in the toucans were not identified. PCR for C. perfringens NetB toxin and enterotoxin genes performed retrospectively on one of the C. perfringens isolates from the second outbreak and on paraffin-embedded tissues from one dead toucan from the first outbreak was negative. With the current C. perfringens toxin typing scheme, C. perfringens type A was identified in the first two outbreaks.